Florida's Bats: Velvety Free-Tailed Bat - Holly K. Ober; Terry J. Doonan; Emily H. Evans (EDIS)
The velvety free-tailed bat is found nowhere in the United States but extreme south Florida. These bats emerge from their roosts earlier than most other bats, often shortly before sunset. This 2-page fact sheet explains how to differentiate velvety free-tailed bats from Brazilian free-tailed bats and Florida bonneted bats. Written by Holly K. Ober, Terry Doonan, and Emily Evans, and published by the UF Department of Wildlife Ecology and Conservation, November 2016.